2020
DOI: 10.3390/jcm9020395
|View full text |Cite
|
Sign up to set email alerts
|

Combined Oral Fentanyl Citrate and Midazolam as Premedication for Bone Marrow Aspiration and Biopsy in Patients with Hematological Malignancies: A Randomized, Controlled and Patient-Blinded Clinical Trial

Abstract: Bone marrow aspiration and biopsy (BMAB) is a painful procedure, and the routinely used local infiltration anesthesia (LIA) with lidocaine is unable to provide pain relief during the most uncomfortable phases. The primary endpoint of the present randomized, patient-blinded trial was to evaluate the efficacy of an opioid and benzodiazepine combination plus LIA (sedoanalgesia) in patients undergoing BMAB for hematological malignancies. The secondary endpoint was the safety of the procedure in an outpatient setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Compared to our study, differences in the applied anesthetics and the standard application of 5.0 ml midazolam 5 mg/ml, a benzodiazepine, could explain the lower reported pain perception. In other settings, a sedoanalgesia combination showed lower levels of perceived pain than analgesia alone [ 22 ]. We decided not to use systemic anxiolytic benzodiazepines to reduce risk of cardiovascular depression, avoid obligatory involvement of anesthesiologists and postoperative monitoring, thus reducing workload, and accelerating the workflow up to, and after the surgery itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to our study, differences in the applied anesthetics and the standard application of 5.0 ml midazolam 5 mg/ml, a benzodiazepine, could explain the lower reported pain perception. In other settings, a sedoanalgesia combination showed lower levels of perceived pain than analgesia alone [ 22 ]. We decided not to use systemic anxiolytic benzodiazepines to reduce risk of cardiovascular depression, avoid obligatory involvement of anesthesiologists and postoperative monitoring, thus reducing workload, and accelerating the workflow up to, and after the surgery itself.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pain perceived during surgery, all authors concluded, that sub-Tenon anesthesia is a valid option, similarly effective as retrobulbar anesthesia, and more effective than peribulbar anesthesia [ 4 , 15 , 17 , 22 ]. Gill et al added that a two-quadrant sub-Tenon injection provided significantly better perioperative anesthesia for vitrectomy compared with a standard single-quadrant technique using the same mixture [ 18 ].…”
Section: Discussionmentioning
confidence: 99%